Prenatal measurement of umbilical cord length using magnetic resonance imaging. (December 2018) - Katsura, Daisuke; Takahashi, Yuichiro; Shimizu, Toshihiro; Watanabe, Yoshihiro; Iwagaki, Shigenori; Murakami, Takashi; Kawabata, Ichiro
Abstract: Objective: This study aimed to evaluate the feasibility of prenatal measurement of umbilical cord length using magnetic resonance imaging (MRI) in comparison with that of postnatal visual measurement. Study design: Patients who underwent MRI pelvimetry to rule out cephalopelvic disproportion were recruited. We compared the umbilical cord length measured prenatally using the three-dimensional image of the umbilical cord constructed by AZE virtual place system (AZE ®, Japan) on MRI (M-length) and measured postnatally using the actual length (R-length). The time interval between MRI scan and birth was set within 4 weeks. Patients were divided into normal, long (>90th centile), and short (<10th centile) groups based on the umbilical cord length. Results: A total of 106 pregnancies were analyzed. MRI was performed at a mean gestational age of 37.4 (34.1–41.7) weeks; the mean gestational age at delivery was 39.4 (36.0–41.8) weeks. M-length and R-length were 67.9 ± 13.6 [mean ± standard deviation] and 57.2 ± 12.7 cm, respectively. The correlation coefficient was larger in the long and short groups than in the normal group. The intraclass correlation coefficient showed high agreement, and Pearson's correlation coefficient revealed correlation inspection as r = 0.702. Bland–Altman analysis indicated non-agreement, and the bias and upper and lower limits of agreement were 10.6 cm and -6.0 and 27.3 cm, respectively. Conclusions: Short and long umbilical cord lengths are associated with perinatal mortality and morbidity. Prenatal measurement of umbilical cord length using MRI is feasible for daily clinical use to distinguish short or long umbilical cords. Further research is needed for more precise clinical application and technical reduction of overestimation errors.